IMPLEMENTATION OF CONFLICT COGNITIVE STRATEGIES IN SCIENCE LEARNING WITH STRUCTURED INQUIRY MODELS TO REDUCE MISCONCEPTIONS ABOUT PRESSURE MATERIAL - Nadia Rahmah Safitri; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aims to describe the reduction of misconceptions about pressure material with conflict cognitive strategies in science learning with structured inquiry models. This study uses a pre-experimental method with One-Group Pretest-Posttest Design. The target of this study was students of VIII-A and VIII-K SMPN 19 Surabaya in the second semester of the school year 2019-2020. The results showed that the percentage of class VIII-A misconceptions was 49.67% and class VIII-K was 60.67%. After learning, the percentage of class VIII-A misconceptions was 3.67% and class VIII-K was 4.33%. From the results of the pretest and posttest, the percentage of misconceptions decreased, with the percentage of class VIII-A decreasing by 46.00% and class VIII-K by 56.33%. The largest shift percentage was from misconceptions to understand the concepts after learning. The effectiveness of learning shown from the results of the N-Gain score, and the results of the N-gain score obtained by 0.938 for class VIII-A and 0.937 for class VIII-K, and both of the classes classified in the high category. Based on the results it can be concluded that the strategy of conflict cognitive in learning science with structured inquiry models can reduce student's misconceptions about pressure material.Keywords: Strategy of conflict cognitive, misconception, structured inquiry